a+b=-3
a*b=-10
aflati a, b
Răspunsuri la întrebare
Răspuns de
0
a+b= -3 |²
(a+b)²= 9
a²+2ab+b²=9
a²+b²+2*(-10)=9
a²+b²-20=9
a²+b²=9+20
a²+b²=29
a+b=-3
a=-3-b
-(3+b)²+b²=29
-(9+6b+b²)+b²=29
-9-6b-b²+b²=29
-9-6b=29
-6b=29+9
-6b=38
b= -6,3
a= -3-(-6,3)= -3 +6,3= 3,3
(a+b)²= 9
a²+2ab+b²=9
a²+b²+2*(-10)=9
a²+b²-20=9
a²+b²=9+20
a²+b²=29
a+b=-3
a=-3-b
-(3+b)²+b²=29
-(9+6b+b²)+b²=29
-9-6b-b²+b²=29
-9-6b=29
-6b=29+9
-6b=38
b= -6,3
a= -3-(-6,3)= -3 +6,3= 3,3
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
Matematică,
10 ani în urmă
Istorie,
10 ani în urmă